Odpowiedź :
Rozwiązanie:
[tex]a)[/tex]
[tex]4^{\sqrt{x-1} }+16=10 \cdot 2^{\sqrt{x-1} }[/tex]
Założenie:
[tex]x-1\geq 0\\x\geq 1[/tex]
Rozwiązanie:
[tex](2^{2})^{\sqrt{x-1} }+16=10 \cdot 2^{\sqrt{x-1} }[/tex]
Podstawmy [tex]t=2^{\sqrt{x-1} }[/tex], gdzie [tex]t>0[/tex] :
[tex]t^{2}+16=10t\\t^{2}-10t+16=0\\\Delta=100-4 \cdot 1 \cdot 16=36\\t_{1}=\frac{10+6}{2}=8\\t_{2}=\frac{10-6}{2}=2[/tex]
Powracamy:
[tex]2^{\sqrt{x-1} }=8 \ \vee \ 2^{\sqrt{x-1} }=2\\2^{\sqrt{x-1} }=2^{3} \ \vee \ 2^{\sqrt{x-1} }=2^{1}[/tex]
Korzystając z tego, że funkcja wykładnicza jest różnowartościowa:
[tex]\sqrt{x-1} =3 \vee \sqrt{x-1}=1\\x-1=9 \vee x-1=1\\x=10 \in D \vee x=2 \in D[/tex]
[tex]b)[/tex]
[tex]2+3^{cos^{2}x}=3^{sin^{2}x}[/tex]
[tex]x \in \mathbb{R}[/tex]
Rozwiązanie:
[tex]2+3^{cos^{2}x}=3^{1-cos^{2}x} \ \ / \cdot 3^{cos^{2}x}\\2 \cdot 3^{cos^{2}x}+(3^{cos^{2}x})^{2}=3[/tex]
Podstawmy [tex]t=3^{cos^{2}x}[/tex], gdzie [tex]t>0[/tex] :
[tex]2t+t^{2}=3\\t^{2}+2t-3=0\\\Delta=4-4 \cdot 1 \cdot (-3)=16\\t_{1}=\frac{-2-4}{2}<0\\t_{2}=\frac{-2+4}{2}=1[/tex]
Wracamy:
[tex]3^{cos^{2}x}=1\\3^{cos^{2}x}=3^{0}[/tex]
Korzystając z tego, że funkcja wykładnicza jest różnowartościowa:
[tex]cos^{2}x=0\\cosx=0\\x=\frac{\pi }{2}+2k\pi \vee x=-\frac{\pi }{2}+2k\pi[/tex]
[tex]c)[/tex]
[tex]9^{x}+3^{x+1}=4[/tex]
[tex]x \in \mathbb{R}[/tex]
Rozwiązanie:
[tex]3^{2x}+3^{x} \cdot 3=4[/tex]
Podstawmy [tex]t=3^{x}[/tex], gdzie [tex]t>0[/tex] :
[tex]t^{2}+3t=4\\t^{2}+3t-4=0\\\Delta=9-4 \cdot 1 \cdot (-4)=25\\t_{1}=\frac{-3+5}{2} =1\\t_{2}=\frac{-3-5}{2}<0[/tex]
Powracamy:
[tex]3^{x}=1\\3^{x}=3^{0}[/tex]
Korzystając z tego, że funkcja wykładnicza jest różnowartościowa:
[tex]x=0[/tex]